Historiografi dari Bawah: Peran Naskah Lokal dalam Merekonstruksi Warisan Ki Mutamakkin - Mu'arifah Mu'arifah; Siska Dwi Purwanti; Retno Widianto; Djono Djono (Universitas Hamzanwadi, 2025)
This article examines the role of Teks Kajen as a form of alternative historiography in reconstructing the spiritual and intellectual legacy of Ki Ahmad Mutamakkin, a controversial figure in Javanese Islamic history. This research aims to answer how local texts such as Serat Sewaka and Manaqib Mutamakkin form a counter-narrative to the official representation in colonial historiography and mainstream religion written in Serat Cebolek. Using a descriptive qualitative method with a critical discourse analysis approach (Fairclough), this study analyzes the narrative structure, Sufistic symbolism, and political dimensions of representation in these texts. The results of the study show that Kajen texts not only function as a medium of devotion and spirituality, but also as a space for articulating epistemic resistance and an agent of community collective memory. This finding confirms the importance of decolonizing Nusantara Islamic historiography and opening space for forms of local knowledge that have been marginalized by official historical narratives.